Oblivion [videorecording (DVD)] - Kosinski, Joseph, 1974-; Cruise, Tom, 1962-; Freeman, Morgan; Leo, Melissa; Kurylenko, Olga, 1979-; Riseborough, Andrea, 1981-; Coster-Waldau, Nikolaj, 1970- (Universal Studios Home Entertainment, 2013)
Jack Harper is the lone security repairman stationed on a desolate, nearly ruined future Earth. When he rescues a beautiful stranger from a downed spacecraft, her arrival triggers a nonstop chain of events that forces him to question everything he knows, and leaves humanity's fate in his hands.